Program Penghijauan Desa melalui Distribusi dan Penanaman 1000 Bibit Buah oleh Mahasiswa KKN Universitas Pertiba di Desa Tukak, Kecamatan Tukak Sadai, Bangka Selatan (Indonesian Version) - Resti Rosanabila; Genta Aditya; Kalista Kalista; Pitriana Pitriana; Sayyid Herdiansyah; Melani Melani; Septiadi Septiadi; Miranti Miranti; Habibilah Fikri; Oktapiani Saputri (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2025)
The Community Service Program (KKN) is a form of student community service aimed at providing tangible contributions to village development. The 2025 KKN Program of Group 04 of Pertiba University was implemented in Tukak Village, Tukak Sadai District, South Bangka Regency, with a primary focus on reforestation activities through the planting and distribution of fruit seedlings. The purpose of this activity is to increase public awareness of the importance of protecting the environment, creating green spaces, and supporting village community food security. The implementation method includes coordination with the village government, provision of seedlings, community outreach, and direct planting of fruit seedlings with village officials, related institutions, and the local community. The results of the activity showed the active involvement of the community and village officials, with the planting and distribution of 1,000 fruit seedlings to all residents of Tukak Village. This activity is expected to create long-term impacts in the form of improving environmental quality, increasing food security, and public awareness of the importance of nature conservation.